2016
DOI: 10.17221/73/2015-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Production value and cost-effectiveness of pig fattening using liquid feeding or enzyme-supplemented dry mixes containing rye grain

Abstract: ABSTRACT:The aim of this study was to assess the cost-effectiveness of a fermented liquid feeding and enzyme supplementation of dry fodders containing rye grain for pig fattening. Two experiments were performed on 126 gilts (82 in Experiment 1 and 44 in Experiment 2) of hybrid Pig Improvement Company (PIC) lines. In both experiments, the pigs were randomly divided into two equinumeric groups (treatment vs control). In Experiment 1, the treatment group received a diet containing 25% of rye grain (cultivar Visel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Because both feed intake and weight gain were reduced in parallel, feed efficiency was not affected by increasing hybrid rye inclusion level. Previous reports feeding rye substituting barley grain showed similar feed efficiency between high rye and barley control diets ( Meyer et al, 2003 ; Schwarz et al, 2014 ; Bussières, 2018 ) whereas others showed better feed efficiency feeding high rye compared with barley control diets ( Thacker et al, 1991 , Thacker and Baas, 1996 ; Schwarz et al, 2016 [only numerically]). The improved feed efficiency feeding rye vs. barley was likely because rye had lower NDF and ADF content than barley grain ( Thacker et al, 1991 ; NRC, 2012 ).…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…Because both feed intake and weight gain were reduced in parallel, feed efficiency was not affected by increasing hybrid rye inclusion level. Previous reports feeding rye substituting barley grain showed similar feed efficiency between high rye and barley control diets ( Meyer et al, 2003 ; Schwarz et al, 2014 ; Bussières, 2018 ) whereas others showed better feed efficiency feeding high rye compared with barley control diets ( Thacker et al, 1991 , Thacker and Baas, 1996 ; Schwarz et al, 2016 [only numerically]). The improved feed efficiency feeding rye vs. barley was likely because rye had lower NDF and ADF content than barley grain ( Thacker et al, 1991 ; NRC, 2012 ).…”
Section: Discussionmentioning
confidence: 85%
“…Loin depth was also not affected because we correctly accounted for differences in AA digestibility between rye and wheat grain when formulating diets. Most other studies that measured carcass characteristics also found no effect of feeding rye on backfat, loin depth, or lean yield ( Hooper et al, 2002 ; Meyer et al, 2003 ; Schwarz et al, 2014 , 2016 ; Villca et al, 2016 ). In one publication, enzyme inclusion in rye diets resulted in greater backfat and smaller loin depth and lean yield ( Schwarz et al, 2016 ) whereas another publication showed a tendency for improved lean yield with enzyme inclusion in rye diets ( Alert and Fröhlich, 2006 ).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Pork, as an indispensable part of agricultural and sideline products for daily life, occupies a dominant position in meat products in China. Pig backfat thickness (PBFT) is a crucial predictor of carcass lean content and meat quality, and as the economic performance, reveals one of the most important breeding targets in pig improvement [2][3][4][5][6][7][8][9] . The PBFT also reflects the growth rate, pork percentage and it has a paramount impact on the reproductive system and also reflects lean meat percentage, and as an important indicator also used to evaluate pork quality grade [4] .…”
Section: Introductionmentioning
confidence: 99%